2018
DOI: 10.1155/2018/1601079
|View full text |Cite
|
Sign up to set email alerts
|

Conventional DCs from Male and Female Lupus-Prone B6.NZM Sle1/Sle2/Sle3 Mice Express an IFN Signature and Have a Higher Immunometabolism That Are Enhanced by Estrogen

Abstract: Type I interferons (IFN) are pathogenic in systemic lupus erythematosus (SLE) and were proposed to control the immunometabolism of dendritic cells (DCs). We previously reported that DCs from female lupus-prone mice constitutively overexpress IFN-responsive genes resembling the IFN signature found in SLE patients. As SLE has higher incidence in women than men, more so in women of reproductive age, estrogens are suggested to affect lupus pathogenesis. We investigated the effects of sex and estrogens on the IFN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Other reports have also supported the idea that metabolic inhibition has greater effect at the post-transcriptional level, with the inhibition of protein translation more evident than the inhibition of RNA transcription (42). We have also previously published a similar discrepancy, as we found that estrogens, by enhancing the immunometabolism of DCs, increase CXCL10 protein but not RNA levels upon TLR stimulation (1). Likewise, in this paper, the effect of EP on the decrease in RNA level is significant but less striking than that on the proteins such as the IL-12p70 and IL-10 cytokines.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Other reports have also supported the idea that metabolic inhibition has greater effect at the post-transcriptional level, with the inhibition of protein translation more evident than the inhibition of RNA transcription (42). We have also previously published a similar discrepancy, as we found that estrogens, by enhancing the immunometabolism of DCs, increase CXCL10 protein but not RNA levels upon TLR stimulation (1). Likewise, in this paper, the effect of EP on the decrease in RNA level is significant but less striking than that on the proteins such as the IL-12p70 and IL-10 cytokines.…”
Section: Discussionsupporting
confidence: 56%
“…We chose the TLR7 ligand R848 because it is a potent murine conventional DC (cDC) activator, which, unlike LPS (38), was not reported to induce DC death. We stained the cells ex vivo for surface lineage markers recognizing cDCs and inflammatory monocytes (iMo), two subsets of innate immune cells that are represented in vitro by the GM-CSF-DCs (1). We observed that the stimulation with R848 induced a decrease in percent splenic cDCs, which was unexpected because R848 was not previously associated with cell death, and an increase in iMo from mLNs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens are also a potential candidate for this bias as the onset of SLE is more frequent in women of childbearing age [32]. A recent study found that estrogens can increase DC maturation, enhance metabolic pathways in DCs, and modulate type I IFN-dependent and type I IFN-independent upregulation of DC activation markers in response to TLR stimulation [33]. Interestingly, estrogens have been shown to affect FcγR expression.…”
Section: Discussionmentioning
confidence: 99%